2006
DOI: 10.1016/j.jcrs.2005.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser in situ keratomileusis and laser-assisted subepithelial keratectomy on retinal nerve fiber layer thickness

Abstract: Laser in situ keratomileusis and LASEK did not significantly affect the RNFL thickness parameters postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 17 publications
2
42
1
2
Order By: Relevance
“…However, when magnification effect was adjusted, no significant association between refractive error and average RNFL thickness was found [7,8]. According to the study results with refractive surgery, RNFL thickness was not significantly affected by corneal refractive surgery [13][14][15]. Salchow et al [16] reported that refractive error change induced by contact lens without astigmatic power (+4, +10, −4, −10 D) did not affect RNFL thickness On the other hand, Lee et al [17] assessed the effect of refractive error change after wearing soft contact lenses of eight different diopters without astigmatic power (−6 to +8) on RNFL thickness measured by Cirrus HD OCT, and reported that RNFL thickness was underestimated in eyes with increasing negative refractive error and overestimated with increasing positive refractive error.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…However, when magnification effect was adjusted, no significant association between refractive error and average RNFL thickness was found [7,8]. According to the study results with refractive surgery, RNFL thickness was not significantly affected by corneal refractive surgery [13][14][15]. Salchow et al [16] reported that refractive error change induced by contact lens without astigmatic power (+4, +10, −4, −10 D) did not affect RNFL thickness On the other hand, Lee et al [17] assessed the effect of refractive error change after wearing soft contact lenses of eight different diopters without astigmatic power (−6 to +8) on RNFL thickness measured by Cirrus HD OCT, and reported that RNFL thickness was underestimated in eyes with increasing negative refractive error and overestimated with increasing positive refractive error.…”
Section: Discussionmentioning
confidence: 77%
“…Various studies investigated the association between refractive error and RNFL thickness [4][5][6][7][8] and the effect of refractive error change induced by refractive surgery [13][14][15] or contact lens [16,17] on RNFL thickness measured by OCT. In cross-sectional studies, average RNFL of myopic eyes was thinner than that of non-myopic eyes [4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that RNFL measurement values determined by scanning laser polarimetry with the fixed corneal compensator are adversely affected by the LASIK procedure, and have raised the concern that the observed changes could be the result of damage induced by the transient elevation of pressure. These changes were not seen when techniques that do not rely on ocular birefringence were used, such as scanning laser tomography or optical coherence tomography [21,22]. Thus, it seemed reasonable to hypothesize that the alterations in RNFL measurements with SLP were artifacts due primarily to a change in the corneal birefringence after LASIK.…”
Section: Discussionmentioning
confidence: 99%